Effect of Different Meltable Binders on the Disintegration and Dissolution Behavior of Zolmitriptan Oromucosal Fast Melt Tablets - Doaa Ahmed El-Setouhy; Emad B. Basalious; Nevine Shawky Abdelmalak (Journal of Pharmacy and Nutrition Sciences, 2017)
Objective: Fast melt tablets and sublingual route have been widely used for providing quick onset of action with the avoidance of first pass metabolism. The objective of this work was to compare the effect of different meltable binders namely; polyethylene glycol (PEG) 4000, pluronic F127 and pluronic F68 on the performance of fast release tablets of the model drug zolmitriptan prepared using the melt granulation technique regarding disintegration time (DT) and dissolution rate (DR) as criteria for rapid absorption and hence quick onset of action. Zolmitriptan is a potent antimigraine drug. Current oral zolmitriptan tablets suffer from slow onset of action, poor bioavailability and large inter-subject variability. Methods: 33 factorial design was adopted. The effect of binder type, binder concentration and croscarmellose sodium (disintegrant) concentration were studied on DT and DR. Results: The three factors were found to significantly affect the DR and the inverse square root of DT and significant interactions were elucidated. Conclusion: Although satisfactory results were obtained regarding DR, modifications using different excipients and or preparation methods should be considered to comply with pharmacopoeia requirement for DT.